Large-Scale Dryland Cropping Systems - A. Schlegel; L. Haag; A. Burnett (Kansas Agricultural Experiment Station Research Reports, 2020)
This study was conducted from 2008–2019 at the Kansas State University Southwest Research- Extension Center near Tribune, KS. The purpose of the study was to identify whether more intensive cropping systems can enhance and stabilize production in rainfed cropping systems to optimize economic crop production, more efficiently capture and utilize scarce precipitation, and maintain or enhance soil resources and environmental quality. The crop rotations evaluated were continuous grain sorghum (SS), wheat-fallow (WF), wheat-corn-fallow (WCF), wheat-sorghum-fallow (WSF), wheat-corn-sorghum-fallow (WCSF), and wheat-sorghum-corn-fallow (WSCF). All rotations were grown using no-tillage practices except for WF, which was grown using reduced-tillage. The efficiency of precipitation capture was not greater with more intensive rotations. Length of rotation had little effect on wheat yields. Corn and grain sorghum yields were about 45–50% greater when following wheat than when following corn or grain sorghum. Grain sorghum yields were about 45% greater than corn in similar rotations.
Keywords: Grain sorghum; corn; wheat; no-till; crop rotations